2018
DOI: 10.3389/fgene.2018.00541
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity-Specific Association Between Ghrelin Leu72Met Polymorphism and Type 2 Diabetes Mellitus Susceptibility: An Updated Meta-Analysis

Abstract: Background: The Leu72Met polymorphism of ghrelin gene has been associated with genetic predisposition to type 2 diabetes mellitus (T2DM), while conclusions remain conflicting. Hence, we performed this updated meta-analysis to clarify the association between Leu72Met polymorphism and T2DM susceptibility.Methods: Six electronic databases were consulted for articles published before 1 January, 2018. Pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated under five genetic models to assess this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(109 reference statements)
1
6
0
Order By: Relevance
“…The frequency for the T allele found in this study is closer to the one (19.1%) reported in East Asian populations [28]. One plausible explanation for the discrepancy between these results is that these studies have focused on European populations, but not on the Balkans [26,[28][29][30]; the present study is the first to report rs696217 allele frequencies among Greek healthy controls.…”
Section: Discussionsupporting
confidence: 51%
“…The frequency for the T allele found in this study is closer to the one (19.1%) reported in East Asian populations [28]. One plausible explanation for the discrepancy between these results is that these studies have focused on European populations, but not on the Balkans [26,[28][29][30]; the present study is the first to report rs696217 allele frequencies among Greek healthy controls.…”
Section: Discussionsupporting
confidence: 51%
“…Recent meta-analysis study by Huang et al . [ 41 ] reported that the GHRL gene Leu72Met variation was possibly protective against T2DM in Caucasians and predisposing in Asians. The consequence of c.214G>T polymorphism is the amino acid substitution Leu72Met.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Steinle et al [40] reported that Met72 allele was associated with metabolic syndrome as well as higher fasting glucose, LDL-C and higher triglyceride levels in the Old Order Amish population. Recent meta-analysis study by Huang et al [41] reported that the GHRL gene Leu72Met variation was possibly protective against T2DM in Caucasians and predisposing in Asians. The consequence of c.214G>T polymorphism is the amino acid substitution Leu72Met.…”
Section: Discussionmentioning
confidence: 99%
“…All of this evidence contributes to the controversial role of this polymorphism in T2D, where its effects in susceptibility varies in different ethnic groups as it has also been described for other human features. It is known that in humans, approximately 15% of the SNP's are population-specific and the differences could be due to the different proportions of SNP alleles in a specific population [16,32]. But at the moment, the underlying mechanisms of molecular evolution of this SNP between different populations is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The Leu72Met polymorphism consists of a transversion of an Cytosine for an Adenine in the position 247 of the GHRL gene, consequently leading to an amino acid change (missense) from Leucine to Methionine in codon 72 [15]. It is known that there is a differential effect of this polymorphism in terms of T2D susceptibility among different ethnic groups [16], so far, there is no evidence about genotypic and allelic frequencies and their association with T2D and in serum ghrelin levels in Mexican population.…”
Section: Introductionmentioning
confidence: 99%